On Indifferentiable Deterministic Hashing into Elliptic Curves (European Journal of Pure and Applied Mathematics, 2017)
In this paper, we give new deterministic encodings based on Elligator`s model, for some families of elliptic curves. These encodings are almost-injective and easily invertible. This allows to make points in the image set of the encoding indistinguishable from uniform string of bits, which is useful for applications in censorship circumvention. Following the idea of Farashahi et al., we show that our encodings are well-distributed. And thus they give rise to hash functions constructions indifferentiable from random oracles.
Keywords: deterministic encodings; elliptic curves; random oracle; indiï¬€erentiable hashing